2011
DOI: 10.1111/j.1365-2648.2011.05694.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients, intimate partners and family experiences of implantable cardioverter defibrillators: qualitative systematic review

Abstract: Patients need additional education, support and follow-up care after hospital discharge. Patients and significant others benefit from collaboration between patient associations and healthcare professional societies. Future research is needed to identify the specific challenges that women recipients face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 63 publications
1
43
0
6
Order By: Relevance
“…Cutitta et al (2014) reported that most patients (64.6%) reported the ability to resume sex, but sexual activity was avoided by 51%. Similar to prior reports, lack of sexual interest, erectile dysfunction (ED), partner overprotectiveness, and fear of the device firing during sexual activity contributed to changes in sexual function (Berg et al, 2013;Palacios-Ceña et al, 2011). Heart failure as a chronic condition also impacts sexual function, with sexual problems experienced by approximately 60% of patients, and up to 81% reporting ED specifically (Jaarsma, Fridlund, & Mårtensson, 2014).…”
Section: Changes In Sexual Activitysupporting
confidence: 57%
“…Cutitta et al (2014) reported that most patients (64.6%) reported the ability to resume sex, but sexual activity was avoided by 51%. Similar to prior reports, lack of sexual interest, erectile dysfunction (ED), partner overprotectiveness, and fear of the device firing during sexual activity contributed to changes in sexual function (Berg et al, 2013;Palacios-Ceña et al, 2011). Heart failure as a chronic condition also impacts sexual function, with sexual problems experienced by approximately 60% of patients, and up to 81% reporting ED specifically (Jaarsma, Fridlund, & Mårtensson, 2014).…”
Section: Changes In Sexual Activitysupporting
confidence: 57%
“…The recovery post-ICD implantation is complex and at times prolonged, placing new demands on significant others who provide support and care. Although there are some recent findings regarding the physical and psychosocial adjustment of patients following ICD implantation (Magyar-Russell et al, 2011; Palacios-Ceña et al, 2011; van den Broek et al, 2011), little is known about the impact of the cardiac illness on the overall health of partners and how this impacts patient recovery. Research indicates that the physical health and psychological well-being of the patient’s intimate partner is important in recovery after cardiac illness (Hwang et al, 2010; Pycha et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Patient post-ICD implantation recovery is associated with a range of physical symptoms, some of which mitigate over time, including palpitations, chest pain, dyspnea, sleep disturbances, loss of libido and fatigue (Palacios-Ceña et al, 2011). Recovery of physical functioning from ICD implantation, particularly for those who receive an ICD for secondary prevention, occurs across 1–2 years, frequently punctuated by health setbacks and ICD shocks (Palacios-Ceña et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Historically, sudden death risk assessment strategies failed to accurately stratify patients. As a consequence, asymptomatic patients often receive ICDs as part of a primary prevention strategy, 4 despite the potential for postimplantation complications, [5][6][7] including anxiety and other psychosocial sequelae. 8,9 Furthermore, significant numbers of recipients have advanced age or comorbidities that serve as competing risks for mortality.…”
Section: T H E Introduction O Fmentioning
confidence: 99%